2014
DOI: 10.1186/1471-2164-15-786
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptome resource for the koala (Phascolarctos cinereus): insights into koala retrovirus transcription and sequence diversity

Abstract: BackgroundThe koala, Phascolarctos cinereus, is a biologically unique and evolutionarily distinct Australian arboreal marsupial. The goal of this study was to sequence the transcriptome from several tissues of two geographically separate koalas, and to create the first comprehensive catalog of annotated transcripts for this species, enabling detailed analysis of the unique attributes of this threatened native marsupial, including infection by the koala retrovirus.ResultsRNA-Seq data was generated from a range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 63 publications
3
60
0
Order By: Relevance
“…In particular, although subtypes C and D have been described previously based upon differences in the hypervariable region (17,19,23), our more detailed analysis revealed that these subtypes in reality belong to a highly diverse paraphyletic group (i.e., subtype D) that contains a number of other subtypes (E, F, G, H, and I) within its component genetic diversity (Fig. 1).…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…In particular, although subtypes C and D have been described previously based upon differences in the hypervariable region (17,19,23), our more detailed analysis revealed that these subtypes in reality belong to a highly diverse paraphyletic group (i.e., subtype D) that contains a number of other subtypes (E, F, G, H, and I) within its component genetic diversity (Fig. 1).…”
Section: Resultsmentioning
confidence: 93%
“…To determine the robustness of individual nodes on the phylogeny, a bootstrap resampling exercise was undertaken, utilizing 1,000 bootstrap replications under the same substitution model defined above but employing NNI branch swapping. Each representative sequence was assigned to a KoRV subtype (A to G) based on clustering within the phylogenetic tree and analysis of patterns of amino acid sequence variation within the hypervariable region, as in previous studies (14,19,20,23).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations